2022
DOI: 10.3390/insects13070641
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Response of Aedes aegypti Larvae to Silver/Silver Chloride Nanoparticles Synthesized Using Bacillus thuringiensis subsp. israelensis Metabolites

Abstract: Silver/silver chloride nanoparticles (Ag/AgCl NPs) are an alternative approach to control the larvae of Aedes aegypti, a vector of mosquito-borne diseases. However, the molecular mechanisms of Ag/AgCl NPs to A. aegypti have not been reported. In this work, Ag/AgCl NPs were synthesized using supernatant, mixed toxins from Bacillus thuringiensis subsp. israelensis (Bti), and heterologously expressed Cry4Aa and Cry4Ba toxins. The images from scanning electron microscopy revealed that the Ag/AgCl NPs were spherica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…The possible mechanism of action of Ag/AgCl NPs against larvae of A. aegypti is through mitochondrial dysfunction, DNA and protein damage, inhibited cell proliferation, and cell apoptosis. Thus, Ag/AgCl NPs are recommended as an alternative method to control A. aegypti, a mosquito-borne disease vector (Chimkhan et al 2022). So that B. subtilis strain LS9.1 results from this study can also be used for the synthesis of green Ag-NPs and prospectively as a biocontrol agent to reduce the A. aegypti mosquito population.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The possible mechanism of action of Ag/AgCl NPs against larvae of A. aegypti is through mitochondrial dysfunction, DNA and protein damage, inhibited cell proliferation, and cell apoptosis. Thus, Ag/AgCl NPs are recommended as an alternative method to control A. aegypti, a mosquito-borne disease vector (Chimkhan et al 2022). So that B. subtilis strain LS9.1 results from this study can also be used for the synthesis of green Ag-NPs and prospectively as a biocontrol agent to reduce the A. aegypti mosquito population.…”
Section: Discussionmentioning
confidence: 86%
“…Geetha et al (2012) reported the need to improve the mosquito adulticidal activity of biosurfactants produced by B. subtilis subtilis. B. subtilis also has been developed as a microbial agent for the green synthesis of silver nanoparticles, a perspective for the control of A. aegypti larvae (Wilson et al 2022;Chimkhan et al 2022). The other studies reported by Bais et al (2004), Fira et al (2018 and Kumbar et al (2019) showed that B. subtilis could be developed for plant pathogens biocontrol agent.…”
Section: Introductionmentioning
confidence: 99%
“…Iftikhar et al (2018), recommended the development of silver nanoparticles produced by B. mojavensis BTCB15, which may play a role in combating mosquito populations, thereby controlling vector-borne diseases. The larvicidal activity of silver nanoparticles (Ag/AgCl NPs) synthesized using Bti supernatant showed that LC50=0.133 g/mL, higher toxicity than that synthesized using insecticidal protein, LC50=0.148-0.217 g/mL (Chimkhan et al 2022). Possible mechanism of action of Ag/AgCl NPs against A. aegypti larvae is through mitochondrial dysfunction, DNA and protein damage, inhibition of cell proliferation, and cell apoptosis, and recommended that Ag/AgCl NPs are an alternative approach to control A. aegypti larvae, a mosquito-borne disease vector (Chimkhan et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…When silenced, larvae were much more tolerant of the toxin, indicating an interesting assistive effect of this protein with the toxin. However, another study found that 2 HSP70 proteins were upregulated in larvae treated with nanoparticles to deliver the Cry4Aa toxin ( 44 ). This may reflect differences in response to the specific toxins.…”
Section: Heat Shock Protein Gene Induction By Insecticidementioning
confidence: 99%